Ambiência e consumo de energia em galpões Dark house para criação de frangos de corte: uso de diferentes tipologias e materiais de fechamento lateral - Ferreira, Jacqueline Cardoso (2017)
The objectives of this study were to evaluate the thermal environment, air quality, energy consumption and efficiency evaluation in two Dark House sheds with lateral sealing made by different materials. Data was collected at nine equidistant points in two commercial warehouses of Granja Agroavicultura Ferreira e Chagas, in the municipality of Prados, MG. The sheds have lateral sealing of different materials, and were identified in GFC (shed with fiber cement side seal) and GIP (siding with Iso Panel seal). The variables environment, temperature, humidity and air velocity were subsidies for calculations of indexes that predict comfort in the breeding environment for broiler chickens: Temperature and Humidity Index (ITU), Globe Temperature and Humidity Index (ITGU), and Enthalpy (H). Measurements of the instantaneous concentrations of ammonia (NH3) and carbon dioxide (CO2) at bird level were taken in the last week of growth, where high concentrations of these gases directly affected yield. The energy consumption of the whole batch was measured with the aid of equipment coupled to the entrance of the energy distribution box in each shed. Production efficiency was calculated based on the data of average weekly weight and feed consumption, and productivity was obtained through the kg of meat produced. It was observed that the GFC shed kept the temperature variable above that recommended as ideal for the last week. Relative air humidity in the GIP shed proved to be below that recommended for the last week. Although variations have occurred between temperature and relative humidity, all the indices calculated for the two sheds are within the ideal developmental ranges recommended by the literature for last week. The levels of ammonia and carbon dioxide present within the facilities were low, indicating adequate air renewal within the handling sheds with the bed used. A low power factor was observed in the GFC shed, indicating the presence of many motors with irregular load distribution. The GIP shed had a higher power factor, but still below the normalized factor. Electricity consumption was higher for the GFC. Despite the fact that the two sheds were within the comfort zones for the sixth week, it was possible to observe that the mass of meat produced (kg m -2 ) was higher for the GIP shed. This can be due to the batch being divided between males and females, and these were housed on the side where higher temperature and low humidity occur, indicating that there was no comfort uniformity in the GFC shed.